A Checklist of Amphibians of Rajasthan, India - Sharma, Indu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Amphibians are cold-blooded animals with dual mode of life and spend part of their lives in water and part on land. They play key role in the Ecosystem, as they are sensitive to slight changes in the environment (climate changes) due to habitat degradation and anthropogenic studies. Thus, present studies will provide base line data and will go a long way for conservation of amphibian fauna. During present studies, 16 species referable to 10 genera, four families from order Anura along with distribution and conservation status from State of Rajasthan has been worked out.